Analisis Pertumbuhan Penjualan Dan Struktur Aktiva Terhadap Struktur Pendanaan Eksternal - Syafrida Hani; Dilla Ainur Rahmi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This research aims to test the correlation between sales growth, assets structure and external funding structure. Result indicates partially,that sales growth did not have correlate to external funding structure, neither do assets structure. Simultaneously, sales growth and assets structure have no correlation to external funding structure. There were mean that external funding structure is affected by another variable outside this research.